Using a smartphone camera to analyse rotating and vibrating systems: Feedback on the SURVISHNO 2019 contest. (1st June 2021) - André, H.; Leclère, Q.; Anastasio, D.; Benaïcha, Y.; Billon, K.; Birem, M.; Bonnardot, F.; Chin, Z.Y.; Combet, F.; Daems, P.J.; Daga, A.P.; De Geest, R.; et al.
Graphical abstract: Highlights: Feedback on the contest organized at the Int. Conf. SURVISHNO 2019. A regular smartphone camera is used to perform advanced mechanical analysis. Estimation of Instantaneous Angular Speed from video analysis. Natural frequencies estimation from video analysis. Rolling shutter effect used to precisely ascertain the frequencies lying beyond the video frame rate. Abstract: A smartphone is a low-cost pocket wireless multichannel multiphysical data acquisition system: the use of such a device for noise and vibration analysis is a challenging task. To what extent is it possible to carry out relevant analysis from it? The Survishno conference, held in Lyon in July 2019, proposed a contest to participants based on this subject. Two challenges were proposed, wherein each a mute video showing an object moving/excited at different frequencies was provided. Due to the frequencies set and the video sampling characteristics, special effects occurred and are visible on both videos. From the first video, participants were asked to estimate the Instantaneous Angular Speed (IAS) of a rotating fan. From the second video, they were asked to perform the modal analysis of a cantilever beam. This paper gathers the interesting ideas proposed by the contestants and proposes a global method to solve these two problems. One major point of the paper might be the advantageous use of the rolling shutter effect, a well-known artefact of smartphone videos, to perform advanced mechanical analyses: the consideration of the unavoidable slight phase shift between the acquisition of each pixel opens up the possibility to perform a dynamic analysis at frequencies that are much higher than the video frame rate.